ZAMONAVIY O‘QUV JARAYONIDA ELEKTRON INTERAKTIV DOSKADA SMART NOTEBOOK ILOVASINI QO‘LLASH - S.P. Kutliyev; H.Farmonov; S.Hilola (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In this article, the use of the smart notebook application on the electronic interactive board and its use in the educational process. Smartnotebook covers the topic of algebraic expressions in practical ways.